Analisa Pengaruh Variasi Perbandingan Roda Gigi Transmisi Untuk Memaksimalkan Daya Listrik Pada Turbin Angin Savonius Bertingkat - Rizky Firmansyah Yunianto; Abdul Wahab; Margianto Margianto (Jurnal Teknik Mesin, 2017)
In line with the increase in the world of economic development. Thus, energy consumption will also increase, particularly in the electrical energy needs. With the more demand for electrical energy will have a negative impact in the absence of new sources of energy that can be used to supply the electrical energy. In this case the wind energy has the potential to be used as a power plant. Wind is moving air because of differences in air temperature. Wind power can be very large and the wind continued presence there and could be one solution to meet the electricity needs. To convert wind energy into electrical energy we need a tool called a wind turbine. The wind turbine itself is a tool that utilizes the driving force for moving the wind to generate electricity. The wind turbine itself is divided into two, namely: horizontal axis wind turbines and vertical axis wind turbines.